Strategy of Project Based Learning (PJBL) Based on Science, Technology, Engineering and Mathematics (STEM) in Growing Active and Creative Students - Asep Dudin Abdul Latip; Asep Supriatna (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The pandemic forced student learning to change, study at home, many new problems were encountered, one of which was a decrease in student activity and creativity. On the other hand, education in the 21st century must be able to facilitate students who are active and creative, adapting to changes in all situations. The aim of this study is to describe the integration of Project Based Learning based on science, technology, eigeneering and mathematics and its success in increasing creative active students. The method used qualitative case study comes from secondary and primary data, observation, documentation, interviews, and triangulation. The results of the study show that the integration of learning goes through the following stages: Pre-Learning Stage, teachers of several subjects collaboratively prepare various tools relevant to the theme; In the implementation phase, students are given the responsibility of completing a project in several weeks. The first week classifies project assignments, divides into groups, provides material, understands worksheets, listens to video links. Worksheet filling, and procurement of materials. The second week is product creation, the third week is completing work sheets, editing videos, making power points, and sending the results to the link. The fourth week is product improvement, the fifth week is the trial, and the sixth week is the work title; In the post-learning stage, evaluation is carried out, and follow-up, reports, dissemination of subject collaboration teams. Its success has increased students' enthusiastic learning attitudes, student creativity, learning enjoyment, competency improvement, and student project products. Keywords: Creative Active Student, Project Based Learning, Technology Eigeneering Mathematics